2022
DOI: 10.3389/fphar.2022.822086
|View full text |Cite
|
Sign up to set email alerts
|

Palatability Assessment of Carbocysteine Oral Solution Strawberry Taste Versus Carbocysteine Oral Solution Mint Taste: A Blinded Randomized Study

Abstract: Objective: To compare and evaluate the palatability of two carbocysteine oral solutions (strawberry vs. mint taste) among healthy children aged 2–12 years.Methods: A randomized, triple-blind, crossover, palatability trial in 42 children aged 2–12 years. All subjects received two preparations of carbocysteine oral solutions (strawberry vs. mint) according to randomized administration sequences, and the administration process was recorded by video. The palatability assessed by emotional valences was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Two previous studies have assessed the use of facial recognition technology to evaluate palatability in the context of medicinal products in children (26,27). However, the main differences of our study compared to the previous studies are as follows.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Two previous studies have assessed the use of facial recognition technology to evaluate palatability in the context of medicinal products in children (26,27). However, the main differences of our study compared to the previous studies are as follows.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, Peng et al (27), used the same software to compare the palatability of two preparations of carbocysteine among healthy children aged 2-12 years. The palatability assessed by emotional valences was performed using a facial action coding system by FaceReader™, which reflected the quantification of emotions; a positive value represents a positive emotion, and a negative value represents a negative emotion (27).…”
Section: Introductionmentioning
confidence: 99%
“…Palatability is an under-recognised factor in drug development that can have a significant impact on long-term treatment adherence among patients and prescribing patterns among physicians 34–38. Studies evaluating the palatability of K + binders12 or other medications35 38 are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Palatability is an under-recognised factor in drug development that can have a significant impact on long-term treatment adherence among patients and prescribing patterns among physicians. [34][35][36][37][38] Studies evaluating the palatability of K + binders 12 or other medications 35 38 are scarce. In one phase I study, three formulations of a calcium-containing polystyrene sulfonate (RDX7675) were evaluated versus SPS.…”
Section: Discussionmentioning
confidence: 99%
“…As recently reviewed by Peng et al (1), the palatability of pediatric pharmaceutical products for children can adversely influence medication compliance. The rejection of unpalatable pharmaceutical products can negatively impact therapeutic adherence which, in turn can lead to treatment failure which may have both immediate consequences (e.g., in the case of oral liquid antimicrobials, persistence of disease) and potentially, delayed consequences (e.g., fostering antibiotic resistance) (2)(3)(4) In a survey of drug administration methods and their relationship to compliance (5), reported that more than 50% of children aged 6 years or less had difficulty swallowing oral drug formulations.…”
Section: Introductionmentioning
confidence: 99%